2014
DOI: 10.1111/jan.12455
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizations of dignity at the end of life: exploring theoretical and cultural congruence with dignity therapy

Abstract: Aim. To explore the conceptualisation of patients' dignity within the context of end-of-life care in Taiwan Background. Dignity therapy (DT) -a novel psychotherapeutic intervention -has been demonstrated to have potential to alleviate terminally ill patients' psycho-existential distress in several western countries. In Taiwan, over half of terminally ill patients experience psychological-spiritual suffering and DT might prove helpful in improving this situation. Hence, a preliminary study to clarify Taiwanese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 45 publications
2
51
0
3
Order By: Relevance
“…A study in Taiwan interviewed 10 palliative care professionals and nine people receiving palliative care about their perceptions of dignity (Li, Richardson, Speck, & Armes, ). The DT framework was generally supported although some divergent themes emerged, such as “living a moral life and acquiescing to God” instead of “maintenance of pride” and “generativity/legacy.” Findings suggested that modifications to DT should be made to ensure it is culturally congruent with Taiwanese beliefs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in Taiwan interviewed 10 palliative care professionals and nine people receiving palliative care about their perceptions of dignity (Li, Richardson, Speck, & Armes, ). The DT framework was generally supported although some divergent themes emerged, such as “living a moral life and acquiescing to God” instead of “maintenance of pride” and “generativity/legacy.” Findings suggested that modifications to DT should be made to ensure it is culturally congruent with Taiwanese beliefs.…”
Section: Resultsmentioning
confidence: 99%
“…Most DT research has taken place in the USA, UK, Canada, and Australia, but studies from Denmark, Sweden, and Taiwan found the question protocol required revision (Houmann et al, 2010;Li et al, 2014;Lindqvist et al, 2014) and a Japanese study found DT to be culturally incompatible (Akechi et al, 2012). These findings suggest that research surrounding the acceptability of DT should be conducted before DT is adopted for use with other cultural groups.…”
Section: Discussionmentioning
confidence: 99%
“…Also, providing a private environment, social support and interactions with others, especially family and healthcare workers are social factors that affect patients' perception of dignity . Recognizing and focusing on these factors will help healthcare workers to preserve and promote patients' dignity (Thompson and Chochinov., 2008;Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…osebnostno (individualno), duhovno, eksistencialno (Šmitek, 2006). Ideja o človeškem dostojanstvu ima pomembno vlogo v filozofiji, teologiji, politiki, zakonodaji kot tudi klinični praksi zdravstvene obravnave (Li, et al, 2014). Z zdravstveno nego je neločljivo povezano spoštovanje človekovih pravic, vključno s kulturnimi pravicami, pravico do življenja in izbire, do dostojanstva in spoštovanja (International Council of Nurses, 2012).…”
Section: Uvodunclassified